1994
DOI: 10.1002/jmri.1880040331
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic heart disease: Assessment with gadolinium‐enhanced ultrafast MR imaging and dipyridamole stress

Abstract: The potential of magnetic resonance (MR) imaging for the detection of myocardial perfusion abnormalities in patients with coronary artery disease has not been fully explored. A feasibility study was conducted in 10 patients with a novel approach to determine whether myocardial ischemia can be assessed with MR imaging and dynamic first-pass bolus tracking enhanced with gadolinium tetraazacyclododecanetetraacetic acid (DOTA). Three tomographic planes were acquired before and after pharmacologic stress with dipyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(52 citation statements)
references
References 10 publications
0
52
0
Order By: Relevance
“…Our results were also excellent compared with prior studies using MRMPI and suggest that the value of MRMPI may have been underestimated. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Two previous studies have compared MRMPI with FFR. In the first study, however, patient numbers were small (nϭ43), and FFR was measured in only 33% of arteries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results were also excellent compared with prior studies using MRMPI and suggest that the value of MRMPI may have been underestimated. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Two previous studies have compared MRMPI with FFR. In the first study, however, patient numbers were small (nϭ43), and FFR was measured in only 33% of arteries.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have compared it with more established techniques such as single-photon emission computerized tomography (SPECT), [1][2][3] positron emission tomography, 4,5 and invasive coronary angiography (CA). 1,[3][4][5][6][7][8][9][10][11][12][13][14][15] It has a number of advantages over the other noninvasive techniques, including high spatial and temporal resolution, no exposure to ionizing radiation, no attenuation or scatter artifacts, and no image orientation constraints. Conventional exercise testing has a sensitivity of 67% and specificity of 72% for correctly identifying patients with significant coronary heart disease (CHD) who have not had a previous myocardial infarction.…”
mentioning
confidence: 99%
“…Thus, these data may seem to be at odds with the results of the present study. However, Lima et al 6 did not perform first-pass imaging. Furthermore, in the present study, all vessels had TIMI grade 3 flow before imaging, whereas the population studied by Lima et al included TIMI 0 to 3 flow.…”
Section: Discussionmentioning
confidence: 99%
“…Previously ischemic, reperfused myocardium has been shown to display 2 different types of contrast "defects": first-pass regions of reduced signal enhancement and regions with relatively increased signal intensity on delayed images. 6,7 The relationship between these 2 patterns and subsequent regional recovery of mechanical function has not been determined. In addition, most previous studies have used only delayed imaging, but it is now possible to image dynamically through the first-pass period.…”
Section: See P 727mentioning
confidence: 99%
“…Thus, it has been reported that increases in the slope and signal intensity of SITC are useful indices for evaluating the degree of myocardial perfusion. [22][23][24] Although the presence or absence of myocardial ischemia may be diagnosed by visually and quantitatively evaluating the first pass kinetics of contrast media using myocardial perfusion MRI, few studies have evaluated the first pass kinetics of contrast media according to the severity of coronary arterial stenosis. Clin-ical evaluation of the severity of coronary arterial stenosis is important to determine the therapeutic strategy for ischemic heart disease.…”
Section: 3-7)mentioning
confidence: 99%